PHYSICAL PROPERTIES OF HYDROGELS AND PVA FILMS BASED ON AQUEOUS NETTLE EXTRACT - LIASHOK, IRINA; KRYUKOVA, OLENA; SHVETS, VYACHESLAV; KYCHUZHYNETS, MAXIM; HALAHAN, VIKTORIIA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article considers the possibility of creating bilayer films and hydrogels from polyvinyl alcohol (PVA) with polysaccharides: potato starch (Kr) and carboxymethyl starch (KMK) based on an aqueous extract of nettle. The rheological properties of PVA, PVA/Cr and PVA/KMK compositions based on the aqueous extract of St. Nettle were studied, and it was established that the PVA solution based on the aqueous extract of St. Nettle and the composition of PVA/KMK solutions are characterized as pseudoplastic liquids, for which the viscosity decreases with increasing shear stresses. And the PVA/Kr composition based on the aqueous extract of St. Nettle belongs to dilatant liquids, that is, systems for which the viscosity increases with an increase in the rate of shear deformation.It was found that the sorption curves of PVA films based on the aqueous extract of stinging nettle have a form characteristic of crystalline polymer materials, the maximum value of sorption of distilled water increases by 27% when starch is added, and by 420% when CMC is added. When starch is added to the film composition, the maximum value of sorption of physiological NaCl solution increases by 35%, the addition of CMC leads to an increase in this indicator by 294%. In general, PVA films based on the aqueous extract of stinging nettle swell less in physiological NaCl solution than in distilled water, by 32%, PVA/Cr – by 24%, and PVA/CMC by 208%.Therefore, the addition of starch to PVA compositions based on an aqueous extract of stinging nettle increases the swelling of films in both distilled water and physiological NaCl solution by almost the same 1.03 times. And the addition of KMC to PVA compositions based on an aqueous extract of stinging nettle increases the swelling of films in distilled water by 1.45 times, and in physiological NaCl solution by 1.3 times. It was established that the addition of starch to the composition of PVA leads to an increase in the degree of swelling of hydrogels based on the aqueous extract of St. Nettle in distilled water and in physiological NaCl solution by 280% less than the addition of KMC. It was found that the addition of KMC to PVA based on nettle extract leads to a decrease in the rate of drying of hydrogels. Recommendations for the use of PVA hydrogels and films based on the aqueous extract of St. Nettle, taking into account the influence of starch and KMC on physical properties, are given.
Keywords: polyvinyl alcohol; water extract of St. Nettle; sorption; physical properties